Iowa Birdline update, February 22, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for February 22, 1993. Highlights of the update include sightings of the continued presence of two Townsend's Solitaires and Two Trumpeter Swans along with Snow Buntings, Lapland Longspurs and Horned Larks. Also included are handwritten notes for the next week's update with sightings of a Short-eared Owl and a Northern Goshawk. Epson - sheet feed/flatbed